Money supply and assets value - Visokavičienė, Birutė (Business: Theory and Practice, 2008)
The aim of this paper is to clarify the role of money supply as the most important target of the classical monetary policy for the price stability, infl ation and economic growth. The theory of monetary policy was developed by observing the money supply. The simple relationship of the monetary policy including all instruments, targets and goals contains a huge number of empirical models which express relationship between money supply and demand, interest rates and asset prices. Accepting all determinations about regulation of money supply including the theory of quantity of money, money supply is described as supplementary function of inflation, interest rate, wealth, human capital, etc. The problem is to determine how the arguments will have influence on the money supply growth, which argument will initiate higher inflation, when and how long monetary policy instruments should be used. Using empirical models we examined relationship between money supply and assets value. Differentiation of the bond and money market was provided by the author using partial derivatives for estimating interaction between interest rates, prices, money supply, and assets value. Pinigų pasiūla ir turto vertė Santrauka. Pastaraisiais metais infliacijos augimas pasaulio ekonomikoje siejamas daugiausia su kylančiomis energinių išteklių kainomis. Tokio pobūdžio infliaciją, kurią lemia importuojamų žaliavų kainos, galima vertinti kaip išorinių veiksnių keliamą grėsmę tolesniam vis daugiau plintančiam kainų augimui, kurį sustabdyti gali tik racionaliai naudojamos pinigų politikos priemonės kartu su fi skalinės politikos priemonėmis. Straipsnyje analizuojama pinigų pasiūlos ir turto vertės sąveika. Pinigų pasiūla (pinigų kiekis) yra svarbiausias pinigų politikos svertas, veikiantis infliaciją, o kartu ir turto vertę. Analizei naudojami metodai ir dėl empirinių tyrimų gautos lygtys, kurias diferencijuodama pagal pinigų ir vertybinių popierių rinkos rodiklius autorė gauna išvestines ir parodo sąveiką tarp palūkanų, kainų, pinigų pasiūlos ir turto vertės. Reikšminiai žodžiai: pinigų politika, pinigų pasiūla, turto vertė, monetariniai instrumentai, svertai. First published online: 19 Sep 2008